El Gorrión Serrano (Xenospiza baileyi): síntesis sobre la historia natural, estudios científicos y acciones para la conservación de un ave micro endémica de México en peligro de extinción - Ortega-Álvarez, Rubén; Calderón-Parra, Rafael; Martínez Molina, Ulises; Martínez Molina, Fredy; Martínez Molina, Gabriel; Martínez Molina, Yuridia; Martínez Villagrán, Agustín; Martínez Freire, Josué; Vásquez Robles, Rocío; García Loaeza, Delfino; Martínez García, Jaciel; García Loaeza, Sarai; et al. (Instituto de Ecología, A.C., 2021)
The conservation of endemic species deserves priority attention given their high vulnerability. Information about the natural history of species is essential for achieving conservation goals. The Sierra Madre Sparrow (Xenospiza baileyi) is an endangered species that is considered to be one of the most vulnerable endemic birds of Mexico (maximum vulnerability value = 20). Its study has been intermittent and the information about its natural history is disperse, unpublished, or difficult to access. This work systematized, evaluated, and updated the knowledge regarding the natural history, taxonomy, description, distribution, habitat, demography, dispersion, territoriality, feeding behavior, ecological interactions, perches, vocalizations, breeding cycle, courtship displays, nest, eggs, nestlings, and threats to the conservation of X. baileyi. In addition, we included novel information generated through community-based monitoring activities, which also highlighted the relevance of including local communities for managing and conserving the species and its habitat. This information is key for optimizing research and guiding urgent conservation actions on the species.